Calon Arang: From Oral Tradition to Text in Pramoedya Ananta Toer’s Narrative for the Advancement of Literary Education - Ayu Suciartini, Ni Nyoman; Payuyasa, I Nyoman (UPT Pusat Penerbitan LP2MPP ISI Bali, 2025)
This study examines the narrative transformation of Calon Arang, a Balinese folklore rich in mysticism and local ethics, into a modern literary text reinterpreted by Pramoedya Ananta Toer. The research assumes that Pramoedya did not merely adapt a folktale but carried out an ideological reconstruction of the character Calon Arang as a symbol of female resistance against structural injustice, gender stigma, and patriarchal epistemological hegemony. In Pramoedya's version, the elderly woman, long portrayed as an evil witch, is reimagined as an intelligent, courageous figure who subverts masculine power structures—both royal and religious. The study employs an intertextual approach and critical discourse analysis by comparing the oral narratives of Calon Arang in Balinese tradition—recorded in lontar manuscripts and dramatized in Calonarang performances—with Pramoedya’s literary text. Using postcolonial feminist theory and Paulo Freire’s critical pedagogy, this research explores the potential of Calon Arang as a teaching material that cultivates both local cultural literacy and critical gender awareness in the classroom. Findings show that the transformation of Calon Arang from oral folklore to modern literary text signifies a paradigmatic shift: from a myth of ostracism to a narrative of resistance. Pramoedya’s Calon Arang emerges not as an emblem of evil but as a metaphor for the educated woman oppressed for resisting sexist norms and unequal socio-religious power. The work is thus relevant for inclusion in secondary and higher education literary curricula as a progressive model of critical literacy rooted in local culture. The study concludes that integrating local folklore into modern literature not only enriches the Indonesian literary canon but also opens dialogic spaces across generations, between myth and social critique, and between education and emancipation. Within the context of the Merdeka Curriculum, this study offers a strategic contribution to the development of contextual, transformative, and gender-sensitive literary education.